115k views
0 votes
X-y=6 and x=y-2; solve by substitution

User Amri
by
5.1k points

2 Answers

7 votes

The solution is

x

=

4

,

y

=

2

Explanation:

x

+

y

=

6

....equation

1

x

y

=

2

.......equation

2

Solving by elimination.

Adding equations

1

and

2

x

+

y

=

6

x

y

=

2

2

x

=

8

x

=

4

Finding

y

by substituting

x

in equation

1

x

+

y

=

6

y

=

6

x

y

=

6

4

y

=

2Explanation:


User Panwar
by
5.1k points
4 votes

Answer: No Solution


Step-by-step explanation: You plug in x=y-2 into x-y=6. So the problem would be rearranged into (y-2)-y=6. When done correctly the y's cancel out making it a no solution.


User Ian L
by
5.1k points